A Comprehensive Literature Review of Management and Quality of Life of Hepatocelullar Carcinoma - Erick Persson Jeffry; Charles Sanjaya Seikka (International Medical Journal Corp. Ltd, 2025)
Background: The management of hepatocellular carcinoma (HCC) is a multifaceted challenge that significantly impacts patients' quality of life (QoL). The literature reveals a growing body of research dedicated to understanding the intricate relationship between HCC management and health-related quality of life (HRQoL), as evidenced by a series of systematic reviews and studies spanning over a decade. Literature Review: The systematic review conducted by (Fan, 2011) underscores that patients with HCC experience a notably poorer HRQoL compared to those with chronic liver disease and the general population. Further, the global survey by (Gill et al., 2018) highlights significant gaps in patient information at diagnosis, with a majority feeling inadequately informed. The exploration of advanced HCC treatment options by (Li et al., 2019) reveals that while curative therapies exist for early-stage HCC, patients often present with advanced disease, where treatment options are limited. The study by (Zhou & Fountzilas, 2019) further examines the impact of systemic therapies on QoL, revealing that side effects from anticancer agents can lead to treatment interruptions, thereby diminishing the overall efficacy of the treatment. This finding highlights the importance of ongoing research to manage drug toxicity and improve the QoL of patients undergoing systemic therapy. The systematic review by (Wohlleber et al., 2021) advocates for standardized HRQoL measures, emphasizing their importance in informing treatment strategies and enhancing patient care. The review also discusses various HRQoL instruments, underscoring the need for their integration into clinical practice to better capture the patient experience. n examining prognostic factors, (Minami et al., 2022) emphasizes the role of early detection and effective management of HCV in improving both survival rates and QoL Conclusion: In conclusion, the literature collectively emphasizes the intricate interplay between HCC management and quality of life. There is a clear need for continued research and enhanced clinical practices that prioritize patient-centered care, effective communication, and the integration of psychosocial support to improve the overall QoL for individuals living with HCC.